Nilai Transaksi E-Money di Indonesia dengan Menggunakan Metode Markov Switching Model - Maratus Zahro; Rika Rahayu (Owner : Riset dan Jurnal Akuntansi, 2021)
The purpose of the research is to examine and analyze the interest rates, inflation rates, stock returns, and holiday conditions on the values of e-money transactions based on two conditions, before and after the issuance of Bank Indonesia regulations. The research data used in this study is the monthly statistical data of the Bank Indonesia payment system for the period 2008-2018. While, the research was the quantitative using the Markov Regime Switching Model and hypothesis testing using time series regression. The research results showed that there was a significant effect between the inflation rate and the value of e-money transactions. In addition, there was an insignificant effect on interest rates, stock returns, and holiday conditions on the value of e-money transactions. This research contributes to the development of economic research by predicting the value of e-money transactions and predicting the value e-money transactions and predicting the turning point of e-money transactions value based on two conditions, before and after the issuance of Bank Indonesia regulations and can be used as input to the government regarding the regulations that issued by Bank of Indonesia, regulations regarding increased the value of e-money transactions.